Post-Covid tourism planning: based on the Azores residents’ perceptions about the development of regional tourism - Sousa, Áurea; Castanho, Rui Alexandre; Couto, Gualter; Pimentel, Pedro (European Planning Studies, 2023)
During 2020, in the context of COVID-19 pandemic, many touristic destinations noticed a drop above 70% of tourists compared to the previous year - 2019. Moreover, some destinations registered a drop in more than 80% in overnight stays compared to 2019. Therefore, in the current period of economic crisis, residents' perceptions of the impacts of tourism may differ substantially from those relating to periods of economic prosperity. Furthermore, the island destinations are more likely to suffer the adverse effects of tourism arising from their inadequate planning. The present study aims to know the current perceptions of residents in an insular region concerning the impacts of tourism development on their islands of residence. In this sense, several statistical methods were used in the scope of a quantitative approach, including some algorithms of Cluster Analysis, and Categorical Principal Component Analysis. Throughout this study, it is possible to identify the “Improve public infrastructure” as the most positive impact of this new tourism paradigm for this ultra-peripheral territory. It becomes clear that the Azores regional actors should follow the sustainable development strategy (including sustainable tourism) if this destination desires to prosper in the post-pandemic period as a potential rural tourism destination.
Keywords: development; insular territories; perceptions; regional studies; tourism planning; Scopus; JCR